2016
DOI: 10.1001/jamaophthalmol.2016.4253
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sports-Related Eye Injuries in the United States

Abstract: IMPORTANCE Ocular trauma can lead to lifelong sequelae, and sports-related ocular injuries have been shown to disproportionately affect the young. Studies quantifying and characterizing the incidence and type of injuries seen with sports-related ocular trauma may be useful for resource utilization, training, and prevention efforts.OBJECTIVE To examine the emergency department (ED) burden of sports-related ocular trauma in the United States.DESIGN, SETTING, AND PARTICIPANTS This retrospective, cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 46 publications
5
63
1
4
Order By: Relevance
“…In a Finnish study of 202 children's eye injuries, 9% of patients were left with a permanent disability; guns, fireworks, tools, and pellet guns were found to be the most dangerous objects. 6 Haring et al 7 found that among sports-related eye injuries in the United States, activities involving projectiles pose the greatest risk for visual impairment in the short term, although in their study long-term outcomes were unavailable.…”
Section: Discussionmentioning
confidence: 97%
“…In a Finnish study of 202 children's eye injuries, 9% of patients were left with a permanent disability; guns, fireworks, tools, and pellet guns were found to be the most dangerous objects. 6 Haring et al 7 found that among sports-related eye injuries in the United States, activities involving projectiles pose the greatest risk for visual impairment in the short term, although in their study long-term outcomes were unavailable.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with previous studies, this study found basketball, baseball and softball, and nonpowder guns to be the most common sports and recreation activities and equipment associated with pediatric eye injury. 7,8 According to the National Eye Institute, the sports with the highest rate of eye injuries are baseball and softball, ice hockey, racquet sports, and basketball. 10 In this study, basketball accounted for the largest proportion of patients with subconjunctival hemorrhage and corneal abrasion.…”
Section: Discussionmentioning
confidence: 99%
“…6 Basketball, baseball and softball, and football, in particular, are commonly associated with eye injury. 7,8 Although sports-and recreationrelated eye injuries are not typically life-threatening, they can result in significant morbidity, including vision loss. Injury is one of the most common causes of monocular blindness, and ∼7% of eye injury patients will have severe vision impairment.…”
mentioning
confidence: 99%
“…A recent study revealed that soccer accounted for almost 7% of all ocular trauma. 117 Approximately 90% of serious eye injuries are preventable through use of appropriate protective eyewear. 118 The AAP and the American Academy of Ophthalmology classify soccer as a moderate-risk sport and strongly recommend that all young participants wear eye protection that meets the American Society for Testing and Materials standard F803, 119 which specifies that protective eyewear be made of polycarbonate, impact-resistant plastic and be worn by all athletes who are functionally monocular or who have a history of major eye surgery or trauma.…”
Section: Protective Equipmentmentioning
confidence: 99%